Implementation Of Learning Concept Of R.A.N.I Model On Mastery Of Mathematics Material At Sdn 04 Koto Ranah Lesson 2015/2016 - Masrida Masrida (Jurnal Ilmiah Pendidikan Scholastic, 2018)
Primary school age around 6-12 years according to Mulyani Sumantri (Teaching and Learning Strategy 2001: 10) is an important and even fundamental development stage for the success of further development. Involvement in group life (collaboration or cooperation) for elementary school age children is of interest and concern. The development of emotional social relationships and the presence of normative ethical awareness in children of this age is a strong feature of elementary school age. Positive and productive social competencies will develop at this age such as the ability to work together, competence, tolerance, kinship and so on. In connection with the above, in the creation of a child learning environment is a development that provides opportunities for children to work in groups is very important. Giving children the opportunity to ask questions and do the questions in front of the classroom with teacher direction is a practical implication of the social-emotional and moral development of primary school-aged children. From the problems above, in the research can be formulated a formula of the problem as follows: Is the existence of the "Rani" approach in the field of mathematics study can enable fourth grade students SDN 04 Koto Ranah District IV Nagari Bayang Utara Pesisir Selatan District Lesson 2015/2016 year teaching activities take place? In this classroom action research, the researcher chose the research method with spriral capital proposed by Kemmis and Mc Taggart (1988), as quoted by Kasihani Kasbolah (2001), that in classroom action research, taking planning steps, (action), evaluation (observation / monitoring) and reflection (reflexion). And so on until the research objectives are achieved. Based on the results of the observation and the results of the problem-solving test, it can be concluded that: Rani's learning model can improve problem solving ability which includes ability to identify problems, determine alternatives, create design, collect data, find solutions and make conclusions on math problems in front of class together on students of Class IV SDN 04 Koto Ranah Sub District IV Nagari Bayang Utara Pesisir Selatan District Lesson Year 2015/2016. The Rani method improves student activity in class discussions on aspects of conveying opinions, responding to opinions and maintaining opinions. Students generally show a positive response to the implementation of the Rani model. This is indicated by the high percentage of students who provide positive and very positive assessment of learning using Rani model.